Food Interactions Observed in a Pharmacokinetic Investigation Comparing Two Marketed Cold Preparations (BNO1016 and ELOM-080) after Administration to Beagle Dogs – A Pilot Study - Seibel, Jan; Neumann, Astrid; Müller, Anne; Wonnemann, Meinolf (Planta Medica, 2022)
Sinupret extract (BNO 1016) and Gelomyrtol forte (ELOM-080) represent the two top-selling cold remedies in Germany nowadays. Whereas BNO 1016 is a typical immediate release coated tablet, ELOM-080 is an enteric-coated soft gelatin capsule. The latter formulation, however, is at risk of pharmacokinetic interactions affecting absorption, especially in cases of concomitant food intake. In the present pilot study, we investigated the risk of a possible food effect in three male beagle dogs. Single doses of BNO 1016 and ELOM-80 were administered under fasting and fed conditions. Blood was sampled up to 30 h post-administration and plasma concentrations of the characteristic ingredients of BNO 1016 as well as ELOM-080 analytes were determined. Pharmacokinetic parameters focusing on the rate and extent of absorption were derived. BNO 1016 analytes demonstrated a similar course in both the fasted and fed states. ELOM-080 analytes also showed a similar picture in the fasted state. However, lag times (time from administration to first quantifiable time point in plasma) of up to 2 h post-administration with corresponding time to reach maximum concentration (obtained directly from the measured concentration) values of 3 to 4 h were observed, reflecting a longer gastric residence time. In the fed state, ELOM-080 showed significant pharmacokinetic characteristics, suggesting a clear food effect. A major observation was a double peak phenomenon that could be observed in two of three dogs. Furthermore, lag times of some analytes, up to 3 – 4 h, and corresponding time to reach maximum concentration values, up to 6 – 8 h, occurred. In contrast to BNO 1016, these findings suggest that, as with other enteric-coated formulations, there may also be a significant risk for food effects with ELOM-080 in humans.
Keywords: enteric-coated drug formulation; food effect; beagle dogs; Sinupret; Gelomyrtol